The Law Enforcement of Corruption Crimes in Terms of Authority Abuse - Yasmirah Mandasari Saragih; Tengku Riza Zarzani (UNISSULA, 2023)
The purpose of writing is to find out and analyze law enforcement in the abuse of authority as a source of corruption. To answer the writing questions that have been formulated above, the authors will use the normative research method. In the legislation regarding the crime of corruption, the element of